ASCERTAINING THE LEVEL OF AWARENESS TOWARDS THE DETERMINANTS OF DELAYED MENSTRUAL PERIOD AMONG STUDENTS OF TERTIARY INSTITUTIONS IN SOUTH-SOUTH - Gbaranor K. B; Biralo P. K.; Mube W. A; Nnadi N. O.; Barinua-Gbaranor N. P.; Umar A. A.; Biibaloo L. L.; Ogbonda N. P.; Mgbere M.; John E. E.; Okoiseh, O. S.; Abdussalam F.; et al. (Web of Journals Publishing, 2025)
Menstrual period is a natural and physiological process that occur regularly or irregularly every month in a woman that have attained puberty. Some interference may cause the monthly menstrual period to be delayed. Some could also occur after six months. Awareness of the determinants of delayed menstrual period is crucial to the young adolescence and young ladies because it actually let them know what could be the possible cause of delay menstrual period when they find themselves in such conditions. The aim of this study is to evaluate The Level of Awareness About the Determinants of Delayed Menstrual Period Among Students of Tertiary Institutions in South-South. The study was a cross-sectional study and a total of 250 female students participated in the study. A well-structured questionnaire was distributed to each participant by the research assistant after consent was granted by the participants. The study was carried out in the six States that make up South-South Geopolitical Zones and it lasted for a period of 3 months (1st April to 30th June, 2023. Data was analyzed with SPSS version 26 and P value < 0.05 was considered significant. The study shows that the students were within 100 level to 600 levels respectively. The study revealed that 96.10% of the students are not aware of the determinants of delayed menstrual period, 98.00% have not had any sex education and 95.6% of the students have not have enlightenment campaingh.
Keywords: Ascertaining, Level, Awareness, Determinants, Delayed.